Pengaruh Profitabilitas dan Leverage Terhadap Pengungkapan Islamic Social Reporting Dengan Ukuran Perusahaan Sebagai Pemoderasi Papa Perusahaan Di JII - Muhamad Yusuf; Nurul Shayida (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effect of profitability and leverage on disclosure of Islamic social reporting with company size as a moderating variable in companies listed in the Jakarta Islamic Index for the period 2013-2017. The study population includes all companies listed in the Jakarta Islamic Index for the 2013-2017 period. Samples were taken using purposive sampling method with certain criteria, during the study period. Based on predetermined criteria and the use of panel data, 85 data can be processed. The data analysis method used is multiple linear regression which is processed using SPSS 20. The results of this study indicate that: (1) profitability has a positive and significant effect on islamic social reporting disclosure. (2) leverage does not affect islamic social reporting disclosure. (3) profitability moderated through company size does not affect on islamic social reporting disclosure. (4) leverage that is moderated through company size has a positive and significant effect islamic social reporting disclosure.